Surgical site infection after hip fracture surgery: a systematic review and meta-analysis of studies published in the UK - Masters, JPM; Metcalfe, D; Ha, JS; Judge, A; Costa, ML (British Editorial Society of Bone and Joint Surgery, 2020)
Aims This study explores the reported rate of surgical site infection (SSI) after hip fracture surgery in published studies concerning patients treated in the UK.